Internet of Things (IoT) Continuity Challenge : Green Energy Power Consumption - Chew, Kim Mey; Yiiong, Siew Ping; Nancy, Bundan; Gary Loh, Chee Wyai; Syvester Tan, Chiang Wei (2021)
The Internet of Things (IoT) has been gaining the attention of various sectors since the promotion in 1990. Billions of physical devices across the globe are connected to the Internet, gathering and sharing all data. The top five challenges have been streamlined as "5C". This study was conducted to address the challenge of "continuity". This research proposed an energy consumption study on the developed solar battery-based IoT water pressure meter. The proposed device has been developed on the basis of the IoT architecture consisting of a perception layer, a network layer and an application layer. Two types of network connectivity have been used: Global System Mobile (GSM) communication and Wi-Fi communication. Two experimental test cases were performed to the study of power consumption. The data collected in the first test case serves as primitive data (indoor) and the second test case serve as comparative data (outdoor). The viability of the battery was examined and presented. The results demonstrated the prolonging of battery life with the improvement on software framework and the increase in the charging rate of solar panels.